Comparison and Co-existence: Sources and Purpose of Authority in the Australian, Madayin and Talmudic Legal Systems - Powell, Claire (Udayana Journal of Law and Culture; Vol 1 No 2 (2017): Rights of the Vulnerable Groups, 2017)
This article will compare Australian, Madayin and Talmudic law in terms of their respective sources and purposes. It will focus on the characterisation of each system to highlight conceptual similarities and differences which affect their operation and, in particular, their commensurability with other systems. Specific areas of law concerned with coexistence are identified as being both crucial and particularly problematic. Notwithstanding Australian government statements and High Court rulings asserting the sovereignty of Australian law, it will be argued that no legal system is self-contained Accommodations are essential and require legislators to grapple with the difficulties of reconciling differing conceptualisations using an informed comparative framework. Talmudic law is considered here as an example of a system which has demonstrated the ability to coexist adaptively with a variety of other systems without compromising its integrity.